2019
DOI: 10.3923/rjmp.2019.129.135
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Medicinal Properties and Possible Nutrient Composition of Citrullus lanatus (Watermelon) Seeds

Abstract: Background and Objective: In countries where cultivation of Citrullu slanatus (watermelon) is on the increase, watermelon is known to have invaluable benefits. Watermelon seeds are often discarded while the fleshy fruit is eaten. This study aimed at determining the medicinal and nutritive bioactive components of Citrullus lanatus through proximate, mineral, vitamin, amino acid and phytochemical analysis. Materials and Methods: In this study, seeds of watermelon were analyzed for proximate, minerals, phytochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…The micronutrient composition of Pterocarpusmildbreadii (Table 1) revealed significant amounts of potassium (K + ), calcium (Ca 2+ ), sodium (Na 2+ ), phosphorus (P 2+ ), iron (Fe 2+ ), manganese (Mn 2+ ), magnesium (Mg 2+ ), Cadium (Cd 2+ ), copper (Cu 2+ ), and zinc (Zn 2+ ). The findings of this study revealed that the outcomes were consistent with previous studies (Enemor, et. al., 2019).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The micronutrient composition of Pterocarpusmildbreadii (Table 1) revealed significant amounts of potassium (K + ), calcium (Ca 2+ ), sodium (Na 2+ ), phosphorus (P 2+ ), iron (Fe 2+ ), manganese (Mn 2+ ), magnesium (Mg 2+ ), Cadium (Cd 2+ ), copper (Cu 2+ ), and zinc (Zn 2+ ). The findings of this study revealed that the outcomes were consistent with previous studies (Enemor, et. al., 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Zinc, on the other hand, was found in the smallest number. As compared to previous work done on seeds by (Enemor, et. al., 2019)no Lead or Cadmium was found.…”
Section: Discussionmentioning
confidence: 69%
“…Overall, aspartate (9.78 g/100 g) was found in higher concentration followed by glutamate (9.65 g/100 g) and arginine (6.55 g/100 g). In a previous study, Enemor et al [2] indicated that the presence of the essential amino acids in the plant under analysis may demonstrate its potential and involvement in body building activities, cell proliferation and stabilization of protein complexes in wound healing. Figure 1 shows the chromatogram obtained for the amino acid profiling of C. longa.…”
Section: Amino Acid Profile Of C Longamentioning
confidence: 99%
“…A vast array of indigenous plants has been employed in the treatment and management of various ailments and illnesses including plants that have served as mere spices for cooking. Enemor et al [2] noted that evidences are also beginning to emerge that even plant seeds hitherto neglected possess, tremendous nutritional and pharmacological potentials. Such plants have not been sufficiently exploited for their nutritional components and potential phytoethnomedicinal properties, hence the need for this study.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, watermelon seeds are an excellent source of dietary oils [135], with high levels of linoleic acid and lower concentrations of oleic, palmitic, and stearic acids, as well as minerals (P, K, Na, and Mg) [136]. Enemor, Oguazu, Odiakosa and Okafor [137] also reported a vast vitaminic repertoire in watermelon seeds, namely vitamins A and C and in minor concentrations B1, B2, B3, B6, B9, B12, D, E, and K. A myriad of other bioactive compounds has been also reported in these seeds, mainly sinapic acid, and lower amounts of other phenols, flavonoids, saponin, tannins, cardiac and cyanogenic glycosides, terpenoids, phytosterol, steroids, and phytates [138,177].…”
Section: Watermelonmentioning
confidence: 99%